(Re) Conceptualising a Social Market Economy for the EU Internal Market - Jotte Mulder (Utrecht University School of Law, 2019)
Can European law legitimately influence or contain the socio-economic orientations of the Member States towards one particular model, and to what extent should it allow or even stimulate a diversity in socio-economic outcomes? This is a fundamental question that lies at the heart of the European Union’s (EU) economic integration project. Many have argued that the concept of the ‘social market economy’ could or should provide for normative guidance. This contribution reflects on the historical and current potential of the concept to provide such guidance. It proposes that the EU internal markets socio-economic diversity should be cherished and accommodated in the legal framework of the EU through a dialogue of mutual responsiveness.